Immunohistochemical characterization of bipolar cells in four distantly related avian species. Issue 4 (22nd December 2022) - Balaji, Vaishnavi; Haverkamp, Silke; Seth, Pranav Kumar; Günther, Anja; Mendoza, Ezequiel; Schmidt, Jessica; Herrmann, Maike; Pfeiffer, Leonie Lovis; Němec, Pavel; Scharff, Constance; Mouritsen, Henrik; Dedek, Karin
Abstract: Visual (and probably also magnetic) signal processing starts at the first synapse, at which photoreceptors contact different types of bipolar cells, thereby feeding information into different processing channels. In the chicken retina, 15 and 22 different bipolar cell types have been identified based on serial electron microscopy and single‐cell transcriptomics, respectively. However, immunohistochemical markers for avian bipolar cells were only anecdotally described so far. Here, we systematically tested 12 antibodies for their ability to label individual bipolar cells in the bird retina and compared the eight most suitable antibodies across distantly related species, namely domestic chicken, domestic pigeon, common buzzard, and European robin, and across retinal regions. While two markers (GNB3 and EGFR) labeled specifically ON bipolar cells, most markers labeled in addition to bipolar cells also other cell types in the avian retina. Staining pattern of four markers (CD15, PKCα, PKCβ, secretagogin) was species‐specific. Two markers (calbindin and secretagogin) showed a different expression pattern in central and peripheral retina. For the chicken and European robin, we found slightly more ON bipolar cell somata in the inner nuclear layer than OFF bipolar cell somata. In contrast, OFF bipolar cells made more ribbon synapses than ON bipolar cells in the inner plexiform layer of these species. Finally, we also analyzed the photoreceptor connectivity of selected bipolar cell types in the European robin retina. In summary, we provide a catalog of bipolar cell markers for different bird species, which will greatly facilitate analyzing the retinal circuitry of birds on a larger scale. Abstract : In the vertebrate retina, bipolar cells are the only interneurons that project from the outer to the inner retina. Here, we systematically tested 12 antibodies for their ability to label individual bipolar cells in the bird retina and compared the eight most suitable antibodies across distantly related species, namely domestic chicken, domestic pigeon, common buzzard, and European robin. In addition, we also analyzed the photoreceptor connectivity of selected bipolar cell types in the European robin retina, which may not only process visual but also magnetic signals.